Knowledge by Presence a Criterion for the Immediacy of Obvious Propositions from the Point of View of Mulla Sadra and Descartes - Ali Kabasizade; Mahdi Dehbashi; Sayyed mohammaddawod alavi (حکمت اسرا, 2023)
AbstractThe attainment of infallible knowledge is a constant concern of philosophers. Accordingly, fundamentalists divide propositions into theoretical and obvious ones, and the reason for the truth of theoretical propositions is their reference to obvious propositions. But why are obvious propositions infallible? These are the questions that this article has tried to address by referring to Sadra’s and Descartes' different views on intuition (Sadra considers intuition synonymous with presence, but Descartes considers simple essences to belong to intuition) and certainty (Sadra believes certainty, as an existential event, is bestowed by the endower of forms (al-Ṣuwar), but Descartes means by certainty the epistemological certainty.) It reveals the fact that knowledge by presence is the criterion and the secret behind the immediacy of the obvious propositions. The difference between the two scholars is that Descartes considers knowledge by presence to be limited to the affective (al-wijdānī) propositions and believes the innate and primary propositions [awwalīyāt] are infallible on account of conceptual clarity. As for Mulla Sadra, it seems that according to him not only the affective and primary propositions but also every acquired knowledge is based on the knowledge by presence. The method of this research is collection, categorize and then analyze and explain the theories of the two philosophers. Finally, inferring ideas of these two philosophers